Honeycomb-shaped porous carbon material for positive electrode of lithium-sulfur battery and preparation method of honeycomb-shaped porous carbon material

The honeycomb-shaped porous carbon material was synthesized by the template method, and the aqueous cerium nitrate solution was soaked and high-temperature carbonization treatment was solved, and the electrochemical performance and cycle life of lithium-sulfur batteries were significantly improved.

CN119528113AActive Publication Date: 2025-02-28CENT SOUTH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411727006.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing porous carbon materials are insufficient in the positive electrode of lithium-sulfur battery, and the polar chemosorption capacity and catalytic conversion capacity need to be improved, resulting in poor electrochemical performance and cycle life of lithium-sulfur battery.

Method used

A honeycomb-like porous carbon material with a three-dimensional structure was synthesized by the template method, and sodium chloride was used as a template and reacted with glucose and thiourea to form sulfur-doped porous carbon, and was soaked through aqueous cerium nitrate solution and carbonized at high temperature to obtain double-doped porous carbon, and finally compounded with lithium sulfide, conductive agent and binder.

Benefits of technology

The specific surface area of ​​porous carbon materials and the exposed area of ​​active centers are improved, the kinetic process of electrochemical reactions is enhanced, the shuttle effect is suppressed, and the electrochemical performance and cycle life of lithium-sulfur batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528113A_ABST
    Figure CN119528113A_ABST
Patent Text Reader

Abstract

The invention discloses a honeycomb-shaped porous carbon material for a positive electrode of a lithium-sulfur battery and a preparation method of the honeycomb-shaped porous carbon material. Amorphous carbon is subjected to pore forming by using a sodium chloride template, cerium atoms are loaded for modification, finally, the porous carbon material with a three-dimensional structure is synthesized through high-temperature carbonization, and the honeycomb-shaped porous carbon material has the advantages that the positive electrode conductivity is enhanced, the positive electrode wettability is improved, and more accommodating space is provided for active substances in the synthesis and charge-discharge processes; more active centers are exposed, and the like. The cerium atoms serving as the active center can be combined with or give electrons, so that the electrochemical reaction electrochemical activity of the lithium-sulfur battery is improved by combining and giving the electrons. And meanwhile, the polarity of the cerium element is higher than that of a transition metal group element, the cerium with a proper content can provide a strong adsorption effect and adsorb polysulfide in the charge-discharge process, adsorption and catalytic conversion combination is realized, the utilization rate of active substances is effectively improved, the shuttle effect is inhibited, the electrochemical performance of the lithium-sulfur battery is improved, and the cycle life of the lithium-sulfur battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy material preparation, and in particular relates to a material for a positive electrode of a lithium-sulfur battery and a preparation method thereof. Background Art

[0002] Lithium-sulfur batteries have the advantages of high theoretical energy density, high theoretical specific capacity, low price, and environmental friendliness, and have become the next generation of energy storage systems that researchers focus on. Lithium-sulfur batteries have obvious advantages, but their inherent disadvantages cannot be ignored, including low positive electrode conductivity, lithium dendrite growth, and shuttle effect, which are problems that lithium-sulfur batteries must overcome in order to be commercialized.

[0003] As supporting materials, porous carbon materials show potential application value in lithium-sulfur battery (Li-S) cathode materials due to their good conductivity, high specific surface area, adjustable pore structure and easy modification. These characteristics enable porous carbon to provide abundant active sites, improve the loading and dispersion of sulfur / lithium sulfide, and enhance the kinetics of electrochemical reactions. However, existing porous carbon materials mostly focus on the modification of non-metallic elements such as nitrogen, sulfur, phosphorus, and boron, and their polar chemical adsorption capacity and catalytic conversion capacity need to be improved. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications and omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art: a method for preparing a honeycomb porous carbon material for a positive electrode of a lithium-sulfur battery, comprising the following steps:

[0007] (1) First, sodium chloride is dissolved in deionized water, stirred vigorously and then ultrasonically dissolved, glucose is added and stirred continuously, the mixed solution is first frozen, and then freeze-dried to obtain a white powder, and the white powder is fully ground and mixed with thiourea;

[0008] (2) After pre-carbonization in a tube furnace, the sodium chloride is washed away with a large amount of clean water, and then vacuum dried to obtain sulfur-doped porous carbon SPC;

[0009] (3) The dried SPC is immersed in a nitrate aqueous solution and stirred, freeze-dried, and then carbonized at high temperature to obtain a dual-doped porous carbon SPC-X;

[0010] (4) SPC-X is compounded with lithium sulfide, a conductive agent and a binder to form a uniform slurry, which is then dried to obtain a honeycomb porous carbon positive electrode.

[0011] Furthermore, the concentration of the sodium chloride aqueous solution in step (1) is 0.05-0.2 g / mL.

[0012] Furthermore, in step (1), the stirring time is 10-30 min, the rotation speed is 200-600 r / min, and the ultrasonic time is 5-30 min.

[0013] Furthermore, the freezing time in step (1) is 8-24 hours, the freezing temperature is -60°C to -80°C; and the freeze-drying time is 36-72 hours.

[0014] Furthermore, in step (1) and step (2), the mass ratio of sodium chloride: glucose: thiourea is 4-30: 0.5-7: 1.

[0015] Further, the concentration of the nitrate (preferably cerium nitrate) in deionized water is 10-30 mg / mL, and the soaking time is 2-6 hours. The inventors found that increasing the concentration of the cerium nitrate aqueous solution will obtain cerium metal clusters or cerium oxide crystals, occupying the pore space of the porous carbon, reducing the space for accommodating active substances, and reducing the atomic efficiency of cerium as a catalytic center, while a lower concentration of cerium nitrate results in poor catalytic effect brought by cerium atoms. Therefore, the optimal concentration of cerium nitrate in deionized water is 10-30 mg / mL.

[0016] Further; the nitrate is: cerium nitrate Ce (NO 3 ) 3 , zinc nitrate Zn(NO), lanthanum nitrate La(NO 3 ) 3 , indium nitrate In(NO 3 ) 3 , iron nitrate Fe (NO 3 ) 3 One or more of .

[0017] Further; the carbonization temperature is 800-1000°C, the heating rate is 1-5°C / min, the calcination time is 2-4h, and the atmosphere is argon or nitrogen.

[0018] In a fourth aspect, in step (4), the mass ratio of SPC-Ce to lithium sulfide, conductive agent, and binder is 2-3:5-6:1:1.

[0019] The beneficial effects of the present invention are as follows:

[0020] (1) The present invention uses a template method to synthesize a honeycomb porous carbon material with a three-dimensional structure. The sodium chloride template is cheap and easily available, and can be easily removed. By adjusting the ratio of glucose to sodium chloride, porous carbon with different specific surface areas can be synthesized, thereby achieving rapid and efficient synthesis of porous carbon. Its porous structure can accommodate more sulfur / lithium sulfide, the active material of the lithium-sulfur battery, and can also increase the exposed area of ​​the active center, thereby improving the utilization rate of the active center.

[0021] (2) The Ce atom as the active center in the present invention can switch freely between +3 valence and +4 valence due to its unique characteristics, and realizes catalytic electrochemical reaction by combining and giving electrons. At the same time, the polarity of cerium element is higher than that of commonly used transition metal elements (including Ni, Co, Mn, Fe, etc.), which can provide strong polar adsorption, realize adsorption + catalytic conversion combination, improve the utilization rate of active materials, inhibit the shuttle effect, and improve the electrochemical performance and cycle life of lithium-sulfur batteries.

[0022] (3) The preparation method of the present invention is scientific, reasonable, easy to implement and low-cost. The obtained porous carbon material has the advantages of simple synthesis and easy adjustment of coordination composition. 2 S / SPC-Ce released high specific capacities of 693, 688, and 679 mAh / g in the first cycle at 0.1C, and the charge and discharge efficiencies in the first three cycles were 99.3%, 98.7%, and 99.7%, respectively. This effectively improved the utilization rate of active materials, suppressed the shuttle effect, and improved the electrochemical performance and cycle life of lithium-sulfur batteries, providing an important reference for the next generation of high-performance lithium sulfide-based lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. The drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0024] Figure 1 SEM of prepared SPC-Ce at different ratios;

[0025] Figure 2 For Li 2 The charge and discharge curves of S / SPC-Ce at 0.1C. DETAILED DESCRIPTION

[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0027] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0028] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0029] A method for preparing a honeycomb porous carbon material for a lithium-sulfur battery positive electrode comprises the following steps:

[0030] (1) First, sodium chloride is dissolved in deionized water, stirred vigorously and then ultrasonically dissolved, glucose is added and stirred continuously, the mixed solution is first frozen, and then freeze-dried to obtain a white powder, and the white powder is fully ground and mixed with thiourea;

[0031] (2) After pre-carbonization in a tube furnace, the sodium chloride is washed away with a large amount of clean water, and then vacuum dried to obtain sulfur-doped porous carbon SPC;

[0032] (3) The dried SPC is immersed in a nitrate aqueous solution and stirred, freeze-dried, and then carbonized at high temperature to obtain a dual-doped porous carbon SPC-X;

[0033] (4) SPC-X is compounded with lithium sulfide, a conductive agent and a binder to form a uniform slurry, which is then dried to obtain a honeycomb porous carbon positive electrode.

[0034] The concentration of the sodium chloride aqueous solution in step (1) is 0.05-0.2 g / mL.

[0035] In step (1), the stirring time is 10-30 min, the rotation speed is 200-600 r / min, and the ultrasonic time is 5-30 min.

[0036] The freezing time in step (1) is 8-24 hours, the freezing temperature is -60°C to -80°C; the freeze-drying time is 36-72 hours.

[0037] In step (1) and step (2), the mass ratio of sodium chloride: glucose: thiourea is 4-30: 0.5-7: 1.

[0038] The concentration of the nitrate (preferably cerium nitrate) in deionized water is 10-30 mg / mL, and the soaking time is 2-6 hours. The inventors found that increasing the concentration of the cerium nitrate aqueous solution will produce cerium metal clusters or cerium oxide crystals, which occupy the pore space of the porous carbon, reduce the space for accommodating active substances, and reduce the atomic efficiency of cerium as a catalytic center, while a lower concentration of cerium nitrate results in poor catalytic effect brought by cerium atoms. Therefore, the optimal concentration of cerium nitrate in deionized water is 10-30 mg / mL.

[0039] The nitrate is: cerium nitrate Ce (NO 3 ) 3 , zinc nitrate Zn(NO), lanthanum nitrate La(NO 3 ) 3 , indium nitrate In(NO 3 ) 3 , iron nitrate Fe (NO 3 ) 3 One or more of .

[0040] The carbonization temperature is 800-1000°C, the heating rate is 1-5°C / min, the calcination time is 2-4h, and the atmosphere is argon or nitrogen.

[0041] In the fourth aspect, in step (4), the mass ratio of SPC-Ce to lithium sulfide, conductive agent, and binder is 2-3:5-6:1:1

[0042] Example 1

[0043] 1. Preparation of SPC

[0044] (1) Dissolve 10 g of sodium chloride in 30 mL of deionized water, stir vigorously for 30 min, and then sonicate for 15 min to completely dissolve it.

[0045] (2) After adding 1.2 g of glucose, the mixture was stirred for 2 h and then immediately placed in a freezer for freezing. The mixture was frozen for 24 h and freeze-dried for 48 h to obtain a white powder.

[0046] (3) The white powder was mixed with 0.6 g of thiourea and ground thoroughly, and heated to 500 °C in an argon atmosphere for calcination for 4 h at a heating rate of 2 °C min -1 , and black powder SPC was obtained.

[0047] 2. Preparation of SPC-Ce

[0048] (1) 0.347 g of cerium nitrate was added to 100 mL of distilled water solution, and then SPC was immersed in the cerium nitrate aqueous solution for 2 h.

[0049] (2) The mixed solution was placed in a freezer for 24 hours, and the black powder obtained after freeze drying for 48 hours was carbonized at 800°C for 2 hours, with a heating rate of 2°C / min and an argon atmosphere. SPC-Ce was obtained after carbonization.

[0050] Figure 1 This is the SEM image of the SPC-Ce obtained in Example 1. From the figure, it can be seen that SPC-Ce has rich mesoporous / macroporous morphology. The rich porous structure is conducive to the infiltration of the electrolyte and the accommodation of more active substances. It is also beneficial to expose the active sites, laying the foundation for achieving good electrochemical performance.

[0051] Example 2

[0052] 1. Preparation of SPC

[0053] (1) Dissolve 20 g of sodium chloride in 30 mL of deionized water, stir vigorously for 20 min, and then sonicate for 30 min to completely dissolve it.

[0054] (2) After adding 2.4 g of glucose, the mixture was stirred for 2 h and then immediately placed in a freezer for freezing. The mixture was frozen for 24 h and freeze-dried for 48 h to obtain a white powder.

[0055] (3) The white powder was mixed with 1.2 g of thiourea and ground thoroughly. The mixture was heated to 600 °C and calcined for 2 h under an argon atmosphere at a heating rate of 2 °C min -1 , and black powder SPC was obtained.

[0056] 2. Li 2 Preparation of S / SPC-Ce

[0057] (1) 0.521 g of cerium nitrate was added to 100 mL of distilled water solution, and then SPC was immersed in the cerium nitrate aqueous solution for 2 h.

[0058] (2) The mixed solution was placed in a freezer for 24 hours, and the black powder obtained after freeze drying for 48 hours was carbonized at 900°C for 2 hours, with a heating rate of 1°C / min and a nitrogen atmosphere. SPC-Ce was obtained after carbonization.

[0059] (3) After SPC-Ce and lithium sulfide are compounded, they are ground and mixed with a conductive agent and a binder in a ratio of 2:6:1:1, stirred, coated and dried to form uniform pole pieces, which are then assembled into lithium-sulfur batteries. 2 The first cycle discharge specific capacity of S / SPC-Ce at 0.1C is 681mAh / g.

[0060] Example 3

[0061] 1. Preparation of SPC

[0062] (1) Dissolve 10 g of sodium chloride in 30 mL of deionized water, stir vigorously for 30 min, and then sonicate for 15 min to completely dissolve it.

[0063] (2) After adding 1.5 g of glucose, the mixture was stirred for 2 h and then immediately placed in a freezer for freezing. The mixture was frozen for 24 h and freeze-dried for 48 h to obtain a white powder.

[0064] (3) The white powder was mixed with 0.6 g of thiourea and ground thoroughly, and heated to 400 °C in an argon atmosphere for calcination for 4 h at a heating rate of 2 °C min -1 , and black powder SPC was obtained.

[0065] 2. Li 2 Preparation of S / SPC-Ce

[0066] (1) 0.694 g of cerium nitrate was added to 100 mL of distilled water solution, and then SPC was immersed in the cerium nitrate aqueous solution for 2 h.

[0067] (2) The mixed solution was placed in a freezer for 24 hours, and the black powder obtained after freeze drying for 48 hours was carbonized at 1000°C for 2 hours, with a heating rate of 2°C / min and a nitrogen atmosphere. SPC-Ce was obtained after carbonization.

[0068] (3) After SPC-Ce is compounded with lithium sulfide, it is ground and mixed with a conductive agent and a binder in a ratio of 3:5:1:1, and the pieces are cut into uniform pole pieces after stirring, coating and drying, and then assembled into a lithium-sulfur battery.

[0069] Figure 2 The charge and discharge curves show that Li 2 S / SPC-Ce released high specific capacities of 693, 688, and 679 mAh / g in the first three cycles at 0.1C, and the charge and discharge efficiencies in the first three cycles were 99.3%, 98.7%, and 99.7%, respectively, indicating that the addition of Ce effectively improved the utilization of active materials, suppressed the shuttle effect, and improved the electrochemical performance and cycle life of lithium-sulfur batteries. These test results provide strong evidence for the practical application of SPC-Ce materials in lithium sulfide-based lithium-sulfur batteries.

[0070] The SPC-Ce prepared according to the method of Experimental Example 3 has a Ce element content of 0.51% (atomic ratio), a C element content of 89.1% (atomic ratio), a N element content of 4.52% (atomic ratio), and a S element content of 5.87% (atomic ratio).

[0071] Comparative Example 1

[0072] Compared with Experimental Example 2, the concentration of the cerium nitrate aqueous solution in the preparation process of Comparative Example 1 was changed to 2 mg / mL, and the other steps were the same. The content of Ce element in the final synthesized sample SPC-Ce was 0.09%, and the content of Ce atoms as the catalytic conversion center was too small. The first cycle capacity at 0.1C was 648 mAh / g, which was 5% lower than that of Experimental Example 2.

[0073] Comparative Example 2

[0074] Compared with Experimental Example 3, Comparative Example 2 removed the immersion in cerium nitrate aqueous solution during the preparation process, and the remaining steps were the same. The final synthesized sample SPC had no Ce element doping, lacked a catalytic center in the structure, and had a first cycle capacity of 643 mAh / g at 0.1C, which was 13% lower than that of Experimental Example 3.

[0075] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a honeycomb porous carbon material for a positive electrode of a lithium-sulfur battery, wherein: The following steps are involved: (1) First, sodium chloride is dissolved in deionized water, stirred vigorously and then ultrasonically dissolved, glucose is added and stirred continuously, the mixed solution is first frozen, and then freeze-dried to obtain a white powder, and the white powder is fully ground and mixed with thiourea; (2) After pre-carbonization in a tube furnace, the sodium chloride is washed away with a large amount of clean water, and then vacuum dried to obtain sulfur-doped porous carbon SPC; (3) The dried SPC is immersed in a nitrate aqueous solution and stirred, freeze-dried, and then carbonized at high temperature to obtain a dual-doped porous carbon SPC-X; (4) SPC-X is compounded with lithium sulfide, a conductive agent and a binder to form a uniform slurry, and the slurry is dried to obtain a honeycomb porous carbon material.

2. The method for preparing a honeycomb porous carbon material for a positive electrode of a lithium-sulfur battery according to claim 1, characterized in that: The concentration of the sodium chloride aqueous solution in step (1) is 0.05-0.2 g / mL.

3. The method for preparing a honeycomb porous carbon material for a positive electrode of a lithium-sulfur battery according to claim 1, characterized in that: In step (1), the stirring time is 10-30 min, the rotation speed is 200-600 r / min, and the ultrasonic time is 5-30 min.

4. The method for preparing a honeycomb porous carbon material for a positive electrode of a lithium-sulfur battery according to claim 1, characterized in that: The freezing time in step (1) is 8-24 hours, and the freezing temperature ranges from -60°C to -80°C; the freeze-drying time is 36-72 hours.

5. The method for preparing a honeycomb porous carbon material for a positive electrode of a lithium-sulfur battery according to claim 1, characterized in that: In step (1) and step (2), the mass ratio of sodium chloride: glucose: thiourea is 4-30: 0.5-7:

1.

6. The method for preparing a honeycomb porous carbon material for a positive electrode of a lithium-sulfur battery according to claim 1, characterized in that: The concentration of the nitrate in deionized water is 10-30 mg / mL, and the soaking time is 2-6 hours.

7. The method for preparing a honeycomb porous carbon material for a positive electrode of a lithium-sulfur battery according to claim 1, characterized in that: The nitrate is one or more of cerium nitrate Ce(NO3)3, zinc nitrate Zn(NO), lanthanum nitrate La(NO3)3, indium nitrate In(NO3)3, and iron nitrate Fe(NO3)3.

8. The method for preparing a honeycomb porous carbon material for a positive electrode of a lithium-sulfur battery according to claim 1, characterized in that: The carbonization temperature is 800-1000°C, the heating rate is 1-5°C / min, the calcination time is 2-4h, and the atmosphere is argon or nitrogen.

9. A honeycomb porous carbon material for a lithium-sulfur battery positive electrode, obtained by the preparation method of a honeycomb porous carbon material for a lithium-sulfur battery positive electrode according to any one of claims 1 to 8, characterized in that: Sodium chloride is used as a pore-forming agent and glucose is used as a main carbon source. In the above process, a dual-doped honeycomb porous carbon is obtained by a simple template method and water washing to remove the template.

10. A honeycomb porous carbon material for a positive electrode of a lithium-sulfur battery according to claim 9, characterized in that: The mass ratio of SPC-Ce to lithium sulfide, conductive agent and binder is 2-3:5-6:1:1.

Citation Information

Patent Citations

  • Micro-nano porous carbon-loaded sulfur composite material prepared by egg white carbonization and preparation method and application thereof

    CN110350176A

  • Preparation method of metal oxide-based composite positive electrode material for lithium-sulfur battery

    CN116470024A

  • Preparation method of high-sulfur-doped porous carbon rich in micropores as well as product and application of high-sulfur-doped porous carbon rich in micropores

    CN116854070A

  • Three-dimensional porous carbon-carbon nitride heterostructure material, preparation method and application thereof, negative plate and application thereof

    CN117594770A

  • Sulfur-doped carbonaceous porous materials

    US20210138431A1